Avaliação do potencial de controle biológico de Guignardia citricarpa (Kiely) fitopatógeno de citros com isolados de Trichoderma SPP - Souza, Kamila Pinto de Azevedo de (My University, 2015)
The culture of citrus is produced worldwide, being consumed in natura or as industrialized products. The citric fruits, such as the orange trees, host many pathogens. The black spot is one disease that affects the citrus culture and has as its usual cause agent Guignardia citricarpa Kiely. The black spot of citrus is more commonly controlled with synthetic pesticides, but this measure has caused undesirable consequences such as the increase of production costs, environment contamination, producers and consumer poisoning. Due to this fact, it is necessary the search for new alternatives of agricultural pesticides of low environmental impact. Since long time ago, several studies have shown the opposite action of several lineages of fungi of genre Trichoderma over other fungi. Although there are studies about the control of Guignardia citricarpa kiely with species of Trichoderma, it is known that the genetic variability of the antagonist and the pathogens show a significant consequence in the efficiency control. This paper has as its objective to evaluate the antagonist capacity of four lineages of Trichoderma spp in controlling Guignardia citricarpa, looking for the identification of isolated ones that could be applied in the citrus cropping in Rio Grande do Sul, with incidence of the black spot. For this study, antagonism tests and volatile compounds tests were carried out with lineages T1A, T4, T17 and T8 of Tricodema spp. Evaluation of enzyme chitinolytic with lineages T1A and T17and evaluation survival of conidium of isolated T1A and T17 de Trichoderma spp in the top part of seedling of orange trees of the Valencia type. The isolated T8, T4, T1A and T17 of Trichoderma spp. in coupled culture show faster speed growing than the isolated A49/11 of Guignardia citricarpa, the same lineages of coupled culture have developed mycoparasitism over the isolated A49/11 of Guignardia citricarpa. The isolated T8, T4, T1A and T17 of Trichoderma spp were capable of inhibiting the mycelia growing of isolated A49/11 of Guignardia citricarpa by emission of volatile metabolites. The isolated T1A and T17 of Trichoderma spp released active chitinases in the presence of non active mycelium of G. citricarpa and Trichoderma spp. The population of Trichoderma spp. sprayed in the top parts of plants sharply reduces in the period of thirty day, however it still maintains a concentration that can possibly acts as a biologic control agent. As a consequence the lineages of Trichoderma spp. used in this paper can be an alternative to synthetic pesticides to control the citrus black spot.
A cultura do citros é produzida mundialmente, sendo consumidos in natura ou na forma de produtos industrializados. Os frutos cítricos são hospedeiros de muitos patógenos. A pinta preta é uma doença que afeta a citricultura, e tem como agente causal Guignardia citricarpa Kiely. A pinta preta dos citros é controlada mais comumente com defensivos sintéticos, mas esta prática tem acarretado em consequências indesejáveis, tais como, aumento do custo de produção, contaminação do meio ambiente, envenenamento de produtores e consumidores. Em vista disso, faz-se necessário a procura por novos defensivos agrícolas alternativos de baixo impacto ambiental. Desde muito tempo, diversos estudos têm mostrado a ação antagônica de inúmeras linhagens dos fungos do gênero Trichoderma sobre outros fungos. Embora existam estudos sobre o controle de Guignardia citricarpa kiely com espécies de Trichoderma, é sabido que a variabilidade genética entre linhagens do antagonista e do patógeno apresentam uma consequência diferencial na eficiência do controle. Este trabalho teve por objetivo avaliar a capacidade antagonista de quatro linhagens de Trichoderma spp sobre Guignardia citricarpa, buscando identificar os isolados que possam ser aplicadas nos cultivos de citros no Rio Grande do Sul, com incidência da pinta preta. Para tal estudo foram feitos teste de antagonismo e teste de compostos voláteis com as linhagens T1A, T4, T17 e T8 de Tricodema spp. Avaliação da atividade enzimática quitinolítica com as linhagens T1A e T17 e avaliação da sobrevivência dos conídeos dos isolados T1A e T17 de Trichoderma spp. na parte aérea das mudas de laranjeira da variedade valência. Os isolados T8, T4, T1A e T17 de Trichoderma spp. em cultura dupla apresentam maior velocidade de crescimento que o isolado A49/11 de Guignardia citricarpa, estas mesmas linhagens em cultura dupla desenvolveram micoparasitismo sobre o isolado A49/11 de Guignardia citricarpa. Os isolados T8, T4, T1A e T17 de Trichoderma spp. foram capazes de inibir o crescimento micelial do isolado A49/11 de Guignardia citricarpa por emissão de metabólitos voláteis. Os isolados T1A e T17 de Trichoderma spp. liberaram quitinases ativas na presença de micélio desativado de G. citricarpa e Trichoderma spp. A população de Trichoderma spp. aspergida na parte aérea das plantas reduz acentuadamente no período de trinta dias, porém ainda mantém uma concentração que possivelmente pode agir como agente de controle biológico. Sendo assim as linhagens de Trichoderma utilizadas neste trabalho podem ser uma alternativa aos defensivos sintéticos para o controle da pinta preta dos citros.
Keywords: Frutas cítricas - Cultivo; Pragas - Controle biológico; Fungos patogênicos; Citrus culture; Pests - Biological control; Pathogenic fungi